Implementation of Ant Colony Optimization Algorithm to Minimize Cost of Turning Process - M. F. F., Ab Rashid; N. M. Z., Nik Mohamed; A. N., Mohd Rose; S. A., Che Ghani; W. S., Wan Harun (Trans Tech Publications, Switzerland, 2015)
In machining process, turning is one of process that were significantly change by introduction of computer numerical control (CNC). However, the process improvement is not stopping there, but the focused has change to reduce the machining cost. Improper parameter selection will caused vibration in cutting, unsecure workpiece, unappealing finishing and cost consuming. Therefore, the optimum parameter setting is required because it related to certain quality characteristics such as the unit production cost. This paper presents the study to minimize production cost for CNC turning process by using Ant Colony Optimization (ACO). The result shows that, the ACO was capable to search for optimum production cost in shorter time compare to other methods, including Genetic Algorithm.